Pemanfaatan Surfaktan Limbah Laundry yang dikombinasikan dengan Ekstrak Serai sebagai Anti Nyamuk Aedes aegypti Linn - ST Aisyah Humaerah; Maming Maming; Syahribulan Syahribulan (University of Halu Oleo, 2021)
This atudy aims to compare the effect of Aedes aegypti mosquito repellent formulations from laundry wastewater combined with various concentrations of lemongrass extract (Cymbopogon nardus L) as an Aedes aegypti mosquito repellent and to prove the effectiveness of mosquito repellent through lethal concentration (LC50) and lethal time (LT50). This study uses an experimental method with a complete randomized plan (RAL) in January-May 2021 at the Laboratory of the Environmental Service, Takalar district and Lab. ILK Entomology Dept. Biology of Hasanuddin University. Formulation of Aedes aegypti mosquito repellent is sample F1 (6:2), F2 (6:1), F3 (6:1.5), F4 (6:0.5) between laundry wastewater and lemongrass extract with an observation time of 8 hours. This study used 300 Aedes aegypti mosquitoes for 3 replications with concentrations of lemongrass extract (8%, 17.5%, 20% and 25%). The ANOVA results showed a significance of P (0.014) < (0.05) which means that the Aedes aegypti mosquito repellent formulation from laundry wastewater combined with various concentrations of lemongrass extract had a very significant effect and the result of the probit analysis found that the value LC50 was 15.04% and an LT50 was 9, 87 minutes. So it can be concluded that the laundry waste combined with various concentrations of lemongrass extract has different effects on the mortality of Aedes aegypti with a level of poison that is quite toxic to the Aedes aegypti mosquito.